Effects of Mycotoxins on the Intestine - Oswald, Isabelle P. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Mycotoxins are secondary metabolites produced by several fungal species. They can contaminate human food and animal feed, and have been a threat for thousands of years. The gastrointestinal tract is the first target when ingesting mycotoxin-contaminated food or feed. As unlikely as it sounds, the investigations concerning the effects of mycotoxins on the intestine are still in their early stages. This book gathers the most recent advances related to the characterization of the intestinal toxicity of mycotoxins. Substantial data assembled on the damage caused to a number of histological structures and functions of the intestine remove any remaining doubt about this organ being a primary target for the toxicity of mycotoxins. An interesting overview of the detrimental effects of mycotoxins on the gut-hosted microbiota—now regarded as a fully-fledged organ associated with the gut—is also given. Finally, outstanding contributions in this book address questions relating to the suitability of current regulations to protect against alterations of the intestine, and to the efficacy assessment of new detoxification strategies using the intestinal toxicity of mycotoxins as a relevant endpoint.